IDENTIFICATION OF FREEMARTINISM IN ZEBU AND CROSSBRED CATTLE - TONK, R K; YADAV, A S; YADAV, B R (The Indian Journal of Animal Reproduction, 2023)
In the present investigations 12 heterosexual twin born calves of different ages and stages from'calf to puberty' were examined. The examination involved physical features, reproductive tract andchromosomal complement. At birth, these animals looked similar to newly born calves of respectivesex, however, females had more coarse hair on the lower lips of vulva. The clitoris got enlarged atpuberty stage and in some cases became tubular structure even visible from distance like glans penis.Rectal palpation of three female co-twins showed underdeveloped infantile reproductive tracts rudimentaryovaries. The chromosomal examination revealed chimaerism as 60,XX/60,XY in all the individuals. However,the proportion of XX complement varied from 41.49 to 76.05 percent and XV varied from 23.94 and 58.51percent among different animals. In four cases both the co-twins were available while only one memberwas available in other four cases. Both the co-twins within sets showed similar proportion of XX /XY cells though it varied in different sets. In the present study the frequency of XX /XY was found to be 41.49: 42.42; 61.48: 59.70; 76.05: 75.49 and 46.89: 44.93 percent in the four pairs, which is reasonablysame in both the co-twins. Six cases were twin born once to their mothers; however, one cow producedtwins thrice. The investigations showed that physical feature help in identification offreemartins, whichcan be confirmed by chromosome examination at birth and rectal palpation at puberty stage.
Keywords: Cattle; Cytogenetic; Chimaerism; Sex Chromosomes